A CIDADE E SEUS LOCAIS: ONDE HÁ CIÊNCIA E TECNOLOGIA? - da Cunha, Marcia Borin (2021)
In today's society, ideas about Science and Technology (CT) are sometimes distorted or inadequate, they stand out, Science is directly linked to the accumulation of knowledge or that Technology is just an essential result of Science. In view of these superficial and undue views on CT, our main issue is the understanding of the perceptions of members of an academic community (university) about CT (the city where they live). Our research was based on the interview technique called Snowboll Sampling (snowball), which made it possible to interview 20 members belonging to the xxx university community. As a result, we can point out that the majority of respondents have as a reference for CT allied to institutional spaces such as universities and research centers. As considerations we point out that it is necessary to expand the scientific culture of the members of this analyzed community, making them aware that the TC in several places.